Our immune system [videorecording] - Agaton, Michael; Bruce, Constance L.; Olsson, Mats Olof; Sandell, Thore (The Society in association with Sandell & Sons., 1988)
Gives a basic understanding of the immune system, how it protects the human body from disease-producing microorganisms. Explores the anatomy and physiology of both the immune system and its enemies - pathogenic microorganisms such as bacteria viruses and parasites. It also introduces AIDS as well as auto-immune diseases.